Analisis Pengaruh Profit Margin dan Price Earning Ratio terhadap Return on Investment: Studi Empiris pada Perusahaan Sektor Tambang yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Abdullah, Mu'ammar; Hendrawan, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The purpose of this study is to examine how the Price Earning Ratio and Profit Margin affect Return on Investment in mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The methodology used in this study is quantitative with multiple linear regression analysis. The results indicate Profit Margin has a significant positive impact on ROI, while the Price Earning Ratio does not show a significant effect. This study suggests that both factors significantly influence ROI, although PER does not demonstrate a significant impat. These findings also provide insights for investor in makin investment decisions and assist companies in improving operational efficiency and financial transparency.